THE IMPACT OF THE APPLICATION OF ONLINE LEARNING SYSTEMS DURING THE COVID-19 PANDEMIC ON THE PSYCHOLOGICAL CONDITION AND LEARNING PERFORMANCE OF STUDENTS - Warsito, Hadi; Darminto, Eko; Hariastuti, Reto Tri; Nuryono, Wiryo (CV. TOTUS TUUS, 2024)
The application of online lectures as a lecture system implemented during the Covid-19 Pandemic is currently seen as a solution to comply with the PSBB policy and to maintain lectures that can continue in accordance with the lecture structure as stated in the Semester Learning Plan. It is undeniable, because of its sudden nature (without being preceded by socialization) there are many complaints. The purpose of this study is to describe the psychological condition of students in participating in online system learning in the Covid-19 pandemic situation and its effect on learning performanceThe results of the study prove that there are significant differences in the psychological condition and learning performance of students between before and after the implementation of the online learning system during the Covid-19 pandemic. The measure of student stress after implementing online learning was significantly higher than the measure of stress. Similarly, there are significant differences in the measure of student learning performance between before and after the implementation of online learning during the Covid-19 pandemic.